Development of Ethnoscience-Based Organic Chemistry Practicum e-Module to Improve Students' Problem Solving Ability - Prasetyo, Yogo Dwi; Syahmani, Syahmani; Dalu, Zaudah Cyly Arrum (Jurnal Pendidikan Sains Universitas Muhammadiyah Semarang, 2023)
This study aims to develop an ethnoscience-based organic chemistry practicum e-Module, determine the feasibility of the developed e-Module, and test its effectiveness in improving the problem-solving abilities of Chemistry Education students. The development procedure in this research is adapted from Thiagarajan (4D), which consists of Define, Design, Develop, and Disseminate. The e-Module trial involved Chemistry Education students at Lambung Mangkurat University, consisting of five people for individual trials, 10 for small group trials, and 19 for field trials. Data was collected using response questionnaires and learning achievement tests. The feasibility test shows that the e-Module is in the very good category based on the assessment of media experts (88%), material experts (90%), and Education experts (89%). Student responses to using e-Modules were also very positive. There is a significant difference between the student's pretest and post-test after using the e-Module with sig <0.05 and experiencing a high increase in students' problem-solving abilities with an N-gain value of 0.77.